PENDIDIKAN AGAMA ISLAM DI SEKOLAH TERPADU (IMPLEMENTASI PAI DI SMA MUTIARA BUNDA) - Aisah, Heti; Ruswandi, Uus; Arifin, Bambang Samsul (Ar-Risalah: Media Keislaman, Pendidikan dan Hukum Islam, 2021)
Religious education subjects in the national curriculum are included in the mandatory curriculum with an allocation of three hours of lessons per week. Graduate competency standards regarding graduate ability qualifications that include attitudes, knowledge and skills. Related to the competence of attitudes that must be possessed by learners in Islamic religious subjects is religious attitudes and social attitudes, where the demands of competence on the ability to live and practice the teachings of Islam in accordance with the demands of basic competencies, both in terms of religion and social side. To achieve this competency, schools that combine the national curriculum and religious excellence curriculum, such as Mutiara Bunda High School. SMA Mutiara Bunda develops islamic religious education content in a religious program. This program refers to the demands of naisonal curriculum, SKL and school visions. Religious programs at Mutiara Bunda High School are carried out in a variety of activities, with different times, such as daily, monthly, semester, yearly and PHBI activities. This study uses a qualitative descriptive approach. The data description is obtained from the results of library studies, observations and interviews. The core of Islamic religious education subjects is the attitude concerning the faith of students, SMA Mutiara Bunda has facilitated it through religious programs.